In Vitro Anticancer Activity and Oxidative Stress Biomarkers Status Determined by Usnea barbata (L.) F.H. Wigg. Dry Extracts - Violeta Popovici; Laura Bucur; Gabriela Vochita; Daniela Gherghel; Cosmin Teodor Mihai; Dan Rambu; Suzana Ioana Calcan; Teodor Costache; Iulia Elena Cucolea; Elena Matei; Florin Ciprian Badea; Aureliana Caraiane; et al. (MDPI AG, 2021)
Lichens represent an important resource for common traditional medicines due to their numerous metabolites that can exert diverse pharmacological activities including anticancer effects. To find new anticancer compounds with fewer side effects and low tumor resistance, a bioprospective study of Usnea barbata (L.) F.H. Wigg. (U. barbata), a lichen from the Călimani Mountains (Suceava county, Romania) was performed. The aim of this research was to investigate the anticancer potential, morphologic changes, wound healing property, clonogenesis, and oxidative stress biomarker status of four extracts of U. barbata in different solvents (methanol, ethanol, acetone, and ethyl acetate), and also of usnic acid (UA) as a positive control on the CAL-27 (ATCC® CRL-2095™) oral squamous carcinoma (OSCC) cell line and V79 (ATCC® CCL-93™) lung fibroblasts as normal cells. Using the MTT assay and according to IC50 values, it was found that the most potent anticancer property was displayed by acetone and ethyl acetate extracts. All U. barbata extracts determined morphological modifications (losing adhesion capacity, membrane shrinkage, formation of abnormal cellular wrinkles, and vacuolization) with higher intensity in tumor cells than in normal ones. The most intense anti-migration effect was established in the acetone extract treatment. The clonogenic assay showed that some U. barbata extracts decreased the ability of cancer cells to form colonies compared to untreated cells, suggesting a potential anti-tumorigenic property of the tested extracts. Therefore, all the U. barbata extracts manifest anticancer activity of different intensity, based, at least partially, on an imbalance in antioxidant defense mechanisms, causing oxidative stress.